The Maieutic Method Combined with Dialectics as the Highest Pedagogical Principle According to Plato - Κουμάκης, Γεώργιος (Education Sciences, 2023)
Plato is the only philosopher in the history of philosophical thought to have stated with particular emphasis that he neither spoke nor wrote his philosophy, because it can neither be spoken nor written like other lessons, due to the inability of logos to satisfactorily grasp the essence of beings. The question which thus inevitably arises is how Plato taught and wrote his philosophy. His own answer is that he used the maieutic method with a latent dialectic, which the student had to reveal in order to create knowledge himself. This means that Plato did not provide his student with ready food, i.e. knowledge, but attempted via appropriate questions to elicit, like a midwife, the answer from his interlocutor. The latter, with a little help, meaning a few indications, finds the answer, thereby giving birth to knowledge. The teacher does not provide knowledge clearly and unambiguously, but in the form of an riddle which the student is called upon to solve, thereby creating knowledge himself; this is achieved through the second stage of the dialectic method, which consists in understanding, i.e. revealing, the teacher’s hidden dialectic. This further means that the riddle, which is put forward in the form of a hidden, latent and unseen dialectic, is presented as the object of inquiry to the student, who by revealing it, i.e. by explaining it with substantiated arguments and by extension solving the presented riddle, gives birth to genuine and autonomous knowledge. The most representative example of a combination of the maieutic and the dialectic method is Plato’s enigmatic and most obscure dialogue, the Parmenides. Thus, in the so-called pedagogical triangle of teacher, student and material taught, the primary role in the autonomous birth of knowledge is played by the method followed. The importance of the appropriate method to the acquisition of knowledge was noted many centuries later by the French philosopher Descartes. Dialectic is consequently the most effective means, the tool, by which, with the teacher’s guidance, knowledge is born during the course of engagement with the issue. This whole process is called the maieutic science or art, since the aim of dialectic is the autonomous production of certain knowledge and high ethos by example, rather than rote learning. The teaching method followed is the primary element and the quintessence of the teaching process. The use of the maieutic method is intended to develop the human critical faculty, providing the cognitive process with an open horizon.